The determinants of corporate hedging decision and effect of hedging strategies on firms'risk: evidence from UK non-financial firms - Dou, Wei (2020)
Since the 1970s, the collapse of the global fixed exchange rate system and violent changes of the global commodity prices, interest rate and exchange rate make the companies produce the safe-haven motive and demand. However, the financial crisis from 2017 to 2019 induced the debate on derivative usage. In this background, this study empirically examines the determinants of hedging by UK non-financial firms. The final dataset comprises 201 UK non-financial companies observed over two years, from 2018 to 2019. Data on hedging activities were manually collected from firms'annual reports. The results of univariate and multivariate tests indicate that expected costs of financial, size, liquidity and foreign exchange rate exposure are significant determinants of firms'derivative hedging activity. Further, there is no evidence that a more inclusive definition of hedging can enhance the ability of models to detect the links between hedging and relevant factors. Finally, ordinary least square regressions provide important evidence that hedging can reduce firms'risk but bring no value to UK non-financial firms.